Pelaksanaan Layanan Administrasi Kesiswaan di MAN 2 Palembang - Setyaningsih, Kris; Sari, Haflah Repi Ulpa; Ibrahim, Ibrahim (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
This research is titled "Implementation of Student Administrative Services at MAN 2 Palembang." The aim of this study is to analyze how the implementation of student administrative services is carried out at MAN 2 Palembang. This research is a field study, employing a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, data verification, and drawing conclusions. The validity of the research data is ensured through source triangulation and technique triangulation. The results of the study indicate that the implementation of student administrative services at MAN 2 Palembang is well underway. The research findings demonstrate that student administrative services at MAN 2 Palembang are effectively executed, encompassing aspects such as effective guidance in the admission of new students, student discipline regulation, guidance and counseling documentation, as well as student learning progress recording. Effective guidance assists students in understanding the process of new student admission clearly, ensuring their comprehension without difficulty, setting clear objectives, and planning strategies to achieve them. Student discipline regulations ensure discipline and responsibility among students, while guidance and counseling documentation provide appropriate guidance and support. Recording student learning progress serves to provide a comprehensive overview of student development and aid them in their educational journey at MAN 2 Palembang.